Retrorectal Schwannomas: Atypical Presentation and Controversial Surgical Management - Wided Trimech; Farouk Ennaceur; Hiba Ben Hassine; Hanen Zneti; Faouzi Noomen; Khadija Zouari (Case Reports in Surgery)
Schwannomas also known as neurilemomas are benign tumors. Retrorectal schwannomas are extremely rare, accounting for 1 to 5% of all schwannomas. They are mostly asymptomatic but may present with symptoms such as pelvic pain, back pain, lower extremities pain, or constipation. Physical examination is often poor. Imaging (CT, MRI) and fine needle biopsy can often help orient the diagnosis. The treatment of choice is monoblock resection of the mass. The prognosis is good. Recurrence has been reported especially after intralesional enucleation. We report a case of a 41-year-old male patient consulting for chronic low back pain eventually diagnosed with retrorectal schwannoma. We performed a surgical resection and the histological examination was consistent with the diagnosis of benign (ancient) schwannoma.